Vertebral morphometrics and lung structure in non-avian dinosaurs. Issue 10 (24th October 2018) - Brocklehurst, Robert J.; Schachner, Emma R.; Sellers, William I.
Abstract : The lung-air sac system of modern birds is unique among vertebrates. However, debate surrounds whether an avian-style lung is restricted to birds or first appeared in their dinosaurian ancestors, as common osteological correlates for the respiratory system offer limited information on the lungs themselves. Here, we shed light on these issues by using axial morphology as a direct osteological correlate of lung structure, and quantifying vertebral shape using geometric morphometrics in birds, crocodilians and a wide range of dinosaurian taxa. Although fully avian lungs were a rather late innovation, we quantitatively show that non-avian dinosaurs and basal dinosauriforms possessed bird-like costovertebral joints and a furrowed thoracic ceiling. This would have immobilized the lung's dorsal surface, a structural prerequisite for a thinned blood-gas barrier and increased gas exchange potential. This could have permitted high levels of aerobic and metabolic activity in dinosaurs, even in the hypoxic conditions of the Mesozoic, contributing to their successful radiation.